2020
DOI: 10.21273/hortsci15136-20
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Air Blowing Device Above Seedbed: The Effect of Air Disturbance on the Microenvironment and Growth of Tomato Seedlings

Abstract: In recent years, air circulation has been used in protected cultivation to improve the microenvironment around seedlings, which in turn enhances photosynthesis and seedling growth. However, a practical and precise air circulation device has not yet been reported, especially one for growing seedlings in a greenhouse. Considering the use of a seedbed in seedling cultivation, a blower that can move back and forth on the seedbed and accurately control the air velocity is designed. In this experiment, we ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…A similar result was observed in the height of tomato seedlings by wind-blowing [68]. The authors also observed that the wind treatment of 0.6 m/s every 30 minute for 5-minute reduced tomato seedlings hardness and elastic modulus by about 25 and 24%, respectively.…”
Section: Mechanical Conditioning Methods For Stem Length Reductionsupporting
confidence: 75%
“…A similar result was observed in the height of tomato seedlings by wind-blowing [68]. The authors also observed that the wind treatment of 0.6 m/s every 30 minute for 5-minute reduced tomato seedlings hardness and elastic modulus by about 25 and 24%, respectively.…”
Section: Mechanical Conditioning Methods For Stem Length Reductionsupporting
confidence: 75%
“…Kitaya et al [12] reported that vertical downwards air currents with airspeeds higher than 0.3 m/s around the plants promoted the photosynthetic and transpiration rates in plants. Another study for the same plant, tomato seedlings, carried out by Li et al [33], suggested that the best effect was seen in the treatment with an air velocity of 0.6 m/s. For sweet potato leaves, Kitaya et al [11] observed that transpiration and net photosynthetic rates were almost constant at air current speeds of 0.3-1.0 m/s.…”
Section: Effect Of Different Opening Angles For the Façade's Panelsmentioning
confidence: 94%
“…Indexes of stem diameter, stem height, and dry mass of seedlings are used to evaluate the health of plant. In previous studies, these indexes are integrated to construct a composite index to describe the plant health comprehensively (Liu et al, 2015;Li et al, 2020). Abscisic acid (ABA) is an endogenous hormone in plants, which has risen significantly under abiotic stress to regulate its physiological activities (Ng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%